2015
DOI: 10.1242/jcs.166439
|View full text |Cite
|
Sign up to set email alerts
|

Analytical cell adhesion chromatography reveals impaired persistence of metastatic cell rolling adhesion to P-selectin

Abstract: Selectins facilitate the recruitment of circulating cells from the bloodstream by mediating rolling adhesion, which initiates the cellcell signaling that directs extravasation into surrounding tissues. To measure the relative efficiency of cell adhesion in shear flow for in vitro drug screening, we designed and implemented a microfluidicbased analytical cell adhesion chromatography system. The juxtaposition of instantaneous rolling velocities with elution times revealed that human metastatic cancer cells, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…2D–F) exhibited a length dependence at 1 μg/mL P-selectin + ICAM-1 and both length and time dependence at 2.5 and 10 μg/mL P-selectin + ICAM-1 at the lowest shear stress tested. Notably, increases in firm adhesion on P-selectin and ICAM-1 co-functionalized substrates from FOV 1 to 3 (78–411% at 0.5 dyn/cm 2 ) could not be accounted for by the less than 5% increase in the number of cells settled on the substrate surface 39 between these locations. This suggests that the length of a substrate available for facilitating cell contact in flow regulates the extent of monocyte firm adhesion, particularly at low wall shear stress.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…2D–F) exhibited a length dependence at 1 μg/mL P-selectin + ICAM-1 and both length and time dependence at 2.5 and 10 μg/mL P-selectin + ICAM-1 at the lowest shear stress tested. Notably, increases in firm adhesion on P-selectin and ICAM-1 co-functionalized substrates from FOV 1 to 3 (78–411% at 0.5 dyn/cm 2 ) could not be accounted for by the less than 5% increase in the number of cells settled on the substrate surface 39 between these locations. This suggests that the length of a substrate available for facilitating cell contact in flow regulates the extent of monocyte firm adhesion, particularly at low wall shear stress.…”
Section: Resultsmentioning
confidence: 88%
“…Substrates were functionalized uniformly with adhesive molecules presented in situ on the inflamed endothelium and since leukocyte recruitment occurs pathophysiologically under low fluid forces typical of the venous circulation 3638 , wall shear stresses ranging from 0.5 to 2.0 dyn/cm 2 were assayed. In conjunction with high speed video microscopy, post-processing of perfusion experiments conducted in such flow systems allowed for quantification of the extents of THP-1 cell rolling adhesion, which is characterized by slow, unsteady forward translation at speeds less than the free flow velocity (free flow velocity > translational velocity > 0) 39 , and firm adhesion (translational velocity = 0) (Fig. S5A).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, length scales relate not only to the initiation of rolling adhesion but also to the formation of firm adhesions, further emphasizing the important role of HEV expansion to increased lymphocyte homing and accumulation in inflamed lymph nodes. We recently demonstrated that the persistence with which cells mediate rolling adhesion to P-selectin is cell subtype dependent (95). Whether the persistence of rolling adhesion to HEVs via other receptors diverges between lymph node–homing cell subtypes, and whether its combined effect with HEV expansion/contraction affects the recruitment of specific lymphocyte subtypes, remains to be elucidated.…”
Section: Lymphatic Transport–directed Remodeling Of the Lymph Nodementioning
confidence: 99%
“…Of the identified extravasation pathways, many are redundant with those of leukocyte homing (Strell and Entschladen, 2008), including interactions between metastatic cell-presented selectin ligands (e.g., sialofucosylated CD44 [Hanley et al, 2006;Subramaniam et al, 2007] and carcinoembryonic antigen [CEA] [Thomas et al, 2008], among others ) with corresponding endothelial-, platelet-, or leukocyte-presented E-, P-, or L-selectin ( Figures 1Aiii and 1Aiv). Given the similarities of these mechanisms with physiologically important homeostatic processes, elucidating cancer cell-specific mechanisms of dissemination is thus crucial to the development of effective therapeutic interventions with highly selective anti-metastatic activity (Li and King, 2012;Oh et al, 2015) and also to the identification of biomarkers for the differentiation of patients with aggressive disease (Baumann et al, 2005;Lech et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Current methods for analyzing single-cell velocities are limited to interrogation via videomicroscopy-based tracking techniques ( Figures 1C and 2). These techniques are not only time consuming but also represent a measured property that cannot be retained by cells for simultaneous off-chip analysis with the molecular mediators that might underlie the heterogeneity of adhesive phenotypes exhibited by metastatic cells that interact with selectins in flow fields ( Figure 1D) and are thought to underlie the process of colon cancer hematogenous metastasis (Edwards et al, 2017;Oh et al, 2015;Reyes-Reyes et al, 2006). Fluorescently tagged antibodies offer a mechanism for labeling cells based on expression of any chosen marker, for example, various adhesive ligands ( Figure 1E), but no such technique exists to ''label'' cells in proportion to their velocity ( Figure 1F).…”
Section: Introductionmentioning
confidence: 99%